2008
DOI: 10.1097/01.nnr.0000313491.94906.8e
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Mass Disaster in the 1950s

Abstract: In the Army Medical Services Department of Atomic Casualties Studies, Werley participated in disaster response classes, nuclear attack simulations, and biomedical research. These efforts fueled Werley's vision for nursing research and interdisciplinary collaboration, resulting in the Army's first department of nursing research. Her actions influenced the nursing community to consider its professional responsibility as a key provider in disaster management and partner in interdisciplinary research. Today, 50 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Universally, nurses constitute the largest group of health care providers and their readiness to respond is crucial for community resilience to disasters (Pang et al, 2009). Since Florence Nightingale's time through to current day, nurses have prepared fellow nurses for patient care around disasters (Leifer and Glass, 2008). Effective patient care in a disaster requires reliable trained teams that form the corner-stone of disaster preparedness (Autrey and Moss, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universally, nurses constitute the largest group of health care providers and their readiness to respond is crucial for community resilience to disasters (Pang et al, 2009). Since Florence Nightingale's time through to current day, nurses have prepared fellow nurses for patient care around disasters (Leifer and Glass, 2008). Effective patient care in a disaster requires reliable trained teams that form the corner-stone of disaster preparedness (Autrey and Moss, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since Florence Nightingale's time through to current day, nurses have prepared fellow nurses for patient care around disasters (Leifer and Glass, 2008). Effective patient care in a disaster requires reliable trained teams that form the corner-stone of disaster preparedness (Autrey and Moss, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…32 Despite the rich history of military nursing research, including the establishment of the first hospital-based nursing research unit in 1954, the uses of research and other evidence in daily clinical practice have not been widely adopted by nursing staff in military facilities. 33,34 The military nursing profession continues to be called upon to pursue and apply best evidence and technology in response to emerging and enduring threats. Yet research utilization scores in Army healthcare settings were found to be significantly lower than those in civilian settings.…”
Section: Evidence-based Nursing Practice In Military Settingsmentioning
confidence: 99%